Forms of Mathematical Representation in the Learning of Fractions of the students of the Fourth Grade of Primary School (GnosisWisdom, 2022)
The present study had the main objective of determining the influence of the application of the forms of mathematical representation in the learning of fractions in the fourth grade of an educational institution of Primary Education. The experimental method has made it possible to explain the effect produced by the application of the different forms of mathematical representation proposed by Marshall and collaborators, as an experimental variable, in the learning of fractions, through the development of learning sessions, which was measured in two moments, with an entrance and exit test with a single group made up of 21 students. The results obtained show that the application of the forms of mathematical representation has allowedgenerate changes in the learning of the fractions of the selected sample, where at the end of the study, 47.6% of students are at the satisfactory level, compared to 0.0% at the beginning of the investigation. It was concluded that the pertinent and permanent application and use of the forms of mathematical representation by students has contributed to the use of cognitive tools, which better understand the notion and solve part-whole fraction problems with continuous and discrete quantities. more effectively.
Keywords: Representation; mathematical representation; part-whole fractions; continuous; discrete quantities